DIAGNOSA PENYAKIT KULIT PADA MANUSIA MENGGUNAKAN METODE FORWARD CHAINING DAN CERTAINTY FACTOR - Piu, Sri Wahyuningsih; Ruktiari, Rima; Aini, Nurul; Hasmin, Erfan (Fakultas Teknik, Universitas Tadulako, 2021)
The skin is the outermost part of the human body tissue that functions to wrap the body and provide protection for the tissues under it. In the human body, the skin includes all general tissues, including facial skin. If the skin has problems such as inflammation, reddish rash, itching, or infection, it can cause skin diseases ranging from mild to severe. In this study, will be explained about a website-based expert system by implementing the Forward Chaining and Certainty Factor methods to help diagnose and calculate the percentage of skin disease, Â so that the general public can recognize the skin diseases they suffer from. The community can detect skin diseases by selecting symptoms and diseases based on the conditions experienced and obtaining information on solutions and early management of the disease they suffer from.